Maternal knowledge to care for children with Beta-Thalassemia: Scoping Review - risnawati, hani; Sumarni, Rantiningsih (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Introduction: Thalassaemia, a genetic disorder prevalent in approximately 7% of the global population, poses significant health challenges, especially in Indonesia, where approximately 2,500 infants are diagnosed annually. The condition commonly manifests as beta thalassaemia, which is classified into major, intermedia and minor forms, with varying degrees of clinical severity and treatment needs. Children with thalassaemia often face chronic health problems that impact their quality of life, requiring lifelong care, including regular blood transfusions and iron chelation therapy. The role of parents, especially mothers, is crucial in the management of thalassaemia, as their knowledge and understanding of the disease significantly affects patient outcomes. Purpose: to assess mothers' knowledge regarding the care of children with beta thalassaemia, Methods: literature review study with systematic search of relevant studies from databases such as Google Scholar, Wiley, and PubMed, published from 2019 to 2024. Results: This review focuses on the correlation between mothers' educational background, understanding of thalassaemia management, and the well-being of affected children. Findings suggest that inadequate maternal knowledge often results in suboptimal care practices, underscoring the need for improved educational programmes and support structures to empower mothers to effectively manage their children's health. Therefore, improving maternal education regarding thalassaemia may lead to better disease management practices, facilitate timely intervention, and ultimately improve the quality of life of children with this genetic disorder. Conclusion: the importance of maternal knowledge both in thalassemia disease and in home care is very important and necessary.